Performance Evaluation of Steel Fibres in Rice Husk Ash Substituted Concretes - A. Sivakumar; V.M. Sounthararajan (Institute for Research and Community Services, Institut Teknologi Bandung, 2013)
The potential use of supplementary cementitious materials in plain cement concrete for improving concrete properties has been a growing concern in recent years. In addition, the effective strengthening of the matrix by fibre reinforcements to avoid brittle failure is another requirement for plain concrete. This provided the motivation for exploring the benefits of rice husk ash (RHA) as a cement replacement material and the addition of steel fibres for reducing brittleness in concrete. The rice husk ash used in this study was the residue of burnt raw rice husk sintered in a muffle furnace at 800 °C. The fine particle size of the rice husk ash provided an early pozzolanic reaction upon cement hydration and thus resulted in high cementing efficiency. This paper reports a systematic evaluation of the mechanical properties of rice husk ash substituted concrete mixtures containing RHA as a partial cement substitute at replacement levels of 10% and 20% by weight of cement, with different dosages of steel fibres. Our experimental results demonstrated that 10% RHA substitution led to improved compressive properties compared to plain concrete. The highest increase of split tensile and flexural strength was reported in the case of RHA substituted concrete with steel fibre added.